“Pure Experience” and the Problem of Order in the Early Philosophy of Nishida Kitarō - Gelūnas, Arūnas (Acta Orientalia Vilnensia, 2001)
The article focuses on the analysis of “pure experience” (junsui keiken), one of the key concepts in the early philosophy of Nishida Kitarō, major Japanese philosopher of the twentieth century, as reflected in his first important book An Inquiry into the Good (Zen no kenkyu). Notwithstanding its Zen Buddhist origin, Nishidean “pure experience” bears strong similarities with the philosophical perspectives of such “psychologically oriented” western thinkers as Wil/iam James and Maurice Merleau-Ponty. Nishida, being in constant dialogue and discussion with the western philosophical tradition, was in constant search of the “logic of the East” as different from that of the West. In contrast to a classical western rationalist position treating perceptive experience as a passive, nebulous and non-discriminating state of consciousness, and reflection as active and creative, Nishida argues for a “systematic character of consciousness” from the very start, “when there is still no subject and object”. Therefore it seems productive for the purposes of the present article to link the concept of “pure experience” to one of the most fundamental philosophical categories, to that of order. For; we strongly believe, it is here that the obvious differences between Nishida and his western counterparts is revealed, bringing him close, however; to the “artistic standpoints” of such western authors as Nietzsche and the above mentioned French phenomenologist Merleau-Ponty.